2013
DOI: 10.1111/aas.12158
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Bispectral Index for monitoring propofol remifentanil anaesthesia. A randomised clinical trial

Abstract: BIS monitoring for guidance of propofol-remifentanil anaesthesia does not result in reduced consumption of anaesthetics and does not reduce time to extubation in adult and children compared with conventional practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
3
13
2
Order By: Relevance
“…Other more recent studies showed similar results to those of our study: For total intravenous anesthesia with propofol and remifentanil in adults and children, Bresil and colleagues showed that the additional use of BIS neither resulted in reduced consumption of anesthetics nor in reduced time to extubation [5]. Additionally, in particular for the sedation of children, Dag and colleagues showed that additional BIS monitoring was not associated with the applied sedative doses, the observed frequency of adverse events, or recovery time [7].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Other more recent studies showed similar results to those of our study: For total intravenous anesthesia with propofol and remifentanil in adults and children, Bresil and colleagues showed that the additional use of BIS neither resulted in reduced consumption of anesthetics nor in reduced time to extubation [5]. Additionally, in particular for the sedation of children, Dag and colleagues showed that additional BIS monitoring was not associated with the applied sedative doses, the observed frequency of adverse events, or recovery time [7].…”
Section: Discussionsupporting
confidence: 90%
“…Both studies used equal or similar sedation regimes and BIS targets to those in our investigation. The median BIS values were 65 [5], 60-70 [7] and 59 in our study. These values reflect deep but not very deep sedation.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…In non-traumatic unconsciousness like during anesthesia, variables derived from electroencephalogram (EEG) like bispectral index (BIS) and cerebral state index (CSI) have been widely used to monitor the depth of anesthesia objectively and quantitatively (2). Among these indices further studies have been undertaken based on BIS (3)(4)(5). Many investigators have tried to broaden the monitoring use of BIS for TBI patients (6,7) and among those many studies found a significant correlation between BIS and GCS (8-11) and some did not (12).…”
Section: Introductionmentioning
confidence: 99%
“…In non-traumatic unconsciousness like during anesthesia, variables derived from electroencephalogram (EEG) like bispectral index (BIS) and cerebral state index (CSI) have been widely used to monitor the depth of anesthesia objectively and quantitatively (2). Among these indices further studies have been undertaken based on BIS (3-5). Many investigators have tried to broaden the monitoring use of BIS for TBI patients (6, 7) and among those many studies found a significant correlation between BIS and GCS (8-11) and some did not (12).…”
Section: Introductionmentioning
confidence: 99%